Improving Survival and Growth of Planted Austrocedrus chilensis Seedlings in Disturbed Patagonian Forests of Argentina by Managing Understory Vegetation - Pafundi, Leticia (2014)
This study was aimed at determining, under field conditions, early interactions between planted cypress seedlings and their associated shrubs in a mesic area of Andean Patagonia and, in a nursery, the effects of increasing light availability on cypress performance when soil water was not a limiting factor. The field experiment was performed in a former cypress–coihue mixed forest (42°02′S, 71°33′W), which was replaced in the 1970s by a plantation of radiata pine. In 2005, 800 cypress seedlings were planted under maqui shrubs in a clear-cut area of the pine stand. In 2007, two treatments were set: no-competition treatment ([NCT] i.e., the surrounding aboveground biomass was removed) and competition treatment ([CT] i.e., without disturbance). The nursery experiment (42°55′S, 71°21′W) consisted of two groups: “shade” (grown under shade cloth) and “sun” (grown at full sun) cypress seedlings. After one growing season, seedling survival and stem growth (in height and diameter) were determined at both sites. Furthermore, the growth rate of leaves, stems, and roots was determined in the nursery. In the field experiment, height growth and survival in NCT were significantly greater than in CT, and a competition process occurred between cypress and surrounding shrubs. In the nursery, sun plants grew more in diameter and increased root weight more than shade plants. Results also showed that in mesic areas of Patagonia, decreasing competition and increasing light levels produced stouter seedlings better adapted to support harsh environmental conditions. Therefore, the removal of protecting shrubs could be a good management practice to improve seedling establishment.